Comparative Analysis of Financial Performance of Firms Listed on the Jakarta Islamic Index - Ariska, Ella; Batubara, Maryam; Syahriza, Rahmi (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2024)
In the context of evaluating company performance, both Economic Value Added (EVA) and Financial Value Added (FVA) provide a comprehensive measure that goes beyond traditional financial ratios, incorporating aspects of value creation for investors and stakeholders. This study aims to address the inconsistencies found in previous research by examining the performance of companies listed on the Jakarta Islamic Index (JII) using EVA and FVA methods. The research employs a quantitative descriptive approach, analyzing data from companies listed on the JII, accessible via the IDX.co.id website. The EVA analysis results for these companies reveal a positive significance, indicating that they are capable of delivering added value to investors. Similarly, the FVA analysis also shows a positive significance, suggesting that companies can enhance investor value, particularly through efficient management of depreciation expenses, which can increase the FVA value. A T-test was conducted to compare the financial performance using EVA and FVA methods, and the results indicate a significant difference between the two, suggesting that the variances are not the same. Both EVA and FVA calculations yield positive results, indicating strong financial performance for the companies analyzed. Notably, the FVA values are found to be greater than the EVA values, underscoring the potential for greater value creation from a financial standpoint. This study contributes to the understanding of how different performance measures can provide insights into company value creation, offering a more nuanced view of financial health for companies listed on the Jakarta Islamic Index.